Leadership wisdom from the monk who sold his Ferrari : the 8 rituals of visionary leaders - Sharma, Robin S. (Robin Shilp), 1964- (Highbridge Audio, 2018)
Enthusiastically embraced by leading organizations such as Microsoft, FedEx, Nortel Networks, IBM, General Motors, and Arthur Andersen, Leadership Wisdom from The Monk Who Sold His Ferrari is one of the most innovative, effective and remarkable books you will ever read on the topic of showing leadership in your work and within your life. Written by leadership guru and renowned professional speaker Robin Sharma, this deeply inspiring work reveals a remarkable step-by-step system that will restore trust, commitment, and spirit within your organization while transforming the way you think, feel, and live in the process. With masterful insight and brilliant simplicity, Robin Sharma has distilled some of the most powerful wisdom available for both professional and personal leadership into eight immensely practical lessons that leaders, managers, and entrepreneurs can immediately apply to send morale and productivity soaring in these topsy-turvy times while creating far more fulfilling inner lives along the way. After reading this book, you will come away feeling genuinely moved to become a true leader who touches lives, adds deeper value to the world, and leaves a beautiful legacy that lasts.